Superficial necrolytic dermatitis: first case report in Indonesia and a literature review - Putra, Andhika; Vimala Putri Lamsundy; Curtis Plowgian (IPB University, 2024)
Superficial necrolytic dermatitis is a rare condition that affects older dogs. It is a fatal disease in which dermatologic signs stem from an abnormality of the liver and/or the pancreas. This paper aims to report a case workup and treatment protocol of superficial necrolytic dermatitis in a patient that presented with lameness. A skin biopsy was performed, and revealed a pathognomonic “red-white-blue” pattern. Abdominal ultrasonography revealed a severe irregular hypoechoic shape nodular pattern and coarse parenchyma with variable size from round and oval. The nodules were surrounded by network of thin hyperechoic strands, forming a “honeycomb/ Swiss cheese-like” pattern. From these findings, a diagnosis of superficial necrolytic dermatitis was made. The patient was treated with a combination of amino acid infusion, liver supplement, and a high-protein diet. However, the patient only lived for four months after diagnosis was made. Clinicians need to be aware that dermatologic lesions may be a manifestation of internal or systemic disease.